Suomen taiteen klassikot - Kämäräinen, Eija; Kämäräinen, Eija; Valkonen, Markku; Wynne-Ellis, Michael (WSOY, 1995)
English summary.
Keywords: 1800-luku; 1900-luku; History; historia; kuvanveistäjät; kuvanveisto; kuvataide; kuvataiteilijat; maalaustaide; suomalaisuus; taide; taidehistoria; taidemaalarit; Art; Finland; Suomi